'Participants of the Divine Nature': The Modern Retrieval of Participation "In Christ" in Paul: Explorations in Paul's Theology of Union and Participation, Michael J.Thate, Kevin J.Vanhoozer and Constantine R.Campbell (eds), Eerdmans, 2018 (ISBN 978‐0‐8028‐7394‐1), x +582 pp., pb 55Participating in Christ: Explorations in Paul's Theology and Spirituality, Michael J.Gorman, Baker Academic, 2019 (ISBN 978‐1‐5409‐6036‐8), xxvi + 296 pp., pb 30Participation in God: A Study in Christian Doctrine and Metaphysics, AndrewDavison, Cambridge University Press, 2019 (ISBN 978‐1‐1084‐8328‐5), xii + 423 pp., hb £75. Issue 2 (11th June 2020) - Dominiak, Paul A.
Abstract: Recent decades have seen a retrieval of the idea of participation in God as a central locus for the Christian faith across all of its ecclesial traditions. 'Participation in God' has two aspects and two registers. It describes the relationship between God and creation and also describes the salvific return of creatures to God as a kind of (re)union with the Creator. These two participatory aspects each have a scriptural register and a philosophical‐theological register. This review article examines what the key claims of participation in God are, why participation aroused suspicion and fell from view, how it has been retrieved in its scriptural and philosophical‐theological registers, and why three recent studies of the idea should be warmly welcomed but cautiously received.